Garland-shaped ZnIn2S4-coated MoO3 photocatalyst, preparation method thereof and application of garland-shaped ZnIn2S4-coated MoO3 photocatalyst in photocatalytic CO2 reduction
The synthesis of the lace-shaped ZnIn2S4@MoO3 photocatalyst by hydrothermal method solved the problems of low conversion efficiency and poor product selectivity in the CO2 reduction process, and achieved efficient CO2 conversion and product selectivity.
Patent Information
- Application Number
- CN202411061020.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photocatalysts have low conversion efficiency during photocatalytic CO2 reduction, poor product selectivity, and it is difficult to meet the needs of CO2 reduction.
The hydrothermal method is used to synthesize the lacquered ZnIn2S4@MoO3 photocatalyst. By controlling the mass and proportion of molybdate, zinc salt, indium salt and sulfur sources, the hydrothermal reaction temperature and time are optimized, and a high specific surface area and optimized differentials are prepared. Photocatalyst at the interface of the junction.
The electron transfer efficiency, CO2 adsorption capacity and reduction efficiency of the photocatalyst are improved, and the CO2 conversion efficiency and product selectivity are significantly improved.
Smart Images

Figure CN119488924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photocatalytic technology, and in particular to a patterned ZnIn2S4@MoO3 photocatalyst, a preparation method thereof, and an application thereof in photocatalytic CO2 reduction. Background Art
[0002] With the massive consumption of fossil fuels, the emission of CO2 in the atmosphere has increased dramatically, causing a series of serious environmental problems such as ocean acidification and global warming. In order to meet this challenge, researchers are actively seeking new ways to capture, store and utilize carbon. Among them, using solar energy to convert CO2 into valuable fuels has become a very promising method. This method can not only effectively reduce the CO2 content in the atmosphere, but also realize the recycling of carbon. In the process of photocatalytic CO2 reduction, CO / CH4 has attracted much attention due to its high energy content and wide application prospects. However, due to the high activation energy of CO2 molecules and the complex reaction process, the conversion efficiency of photoreduction of CO2 and H2O to generate CH4 is low, and the product selectivity is poor. Therefore, how to design an efficient photocatalytic CO2 reduction catalyst has become an urgent problem to be solved.
[0003] In recent years, the research community has shown an increasing interest in multi-component layered metal sulfide materials. These materials have been very successful in visible light-responsive photocatalytic applications due to their excellent narrow bandgap characteristics and unique electronic and optical properties. Among them, ZnIn2S4, as a representative of layered AB2X4 ternary metal sulfides, has become a research focus in the fields of energy and environmental protection due to its unique layered structure and excellent stability. ZnIn2S4 has a unique layered structure, consisting of unit layers such as (Zn-S)-(S-In-S)-(In-S) stacked layer by layer along the z-axis. In this structure, the In-S layer and the Zn-S layer play the core roles of the conduction band minimum (CBM) and valence band maximum (VBM) orbits, respectively. Under the action of light, photogenerated electrons can efficiently transition from the VBM of the Zn-S layer to the CBM of the In-S layer, and then participate in the key reduction reaction. The asymmetric layered structure of ZnIn2S4 makes it possible to induce a built-in electric field and regulate charge dynamics.
[0004] At present, the research on ZnIn2S4 photocatalysts in this field is mainly focused on photolysis of water to produce hydrogen. For example, the Chinese invention patent with publication number CN112495401A discloses a Mo-doped MoO3@ZnIn2S4Z system photocatalyst and its preparation method and application. The invention uses a one-step solvothermal method to construct a Mo-doped and Z-system photocatalyst. The impurity energy level is introduced by Mo doping to improve the separation efficiency of carriers and expand the light absorption of the catalyst, reduce the overpotential of hydrogen production, and extend the life of the excited state. The construction of the MoO3@ZnIn2S4Z system photocatalyst can enhance the redox potential of the photocatalyst. ZnIn2S4 is uniformly loaded on the surface of MoO3, which can avoid its own agglomeration and expose more active sites. For example, the Chinese invention patent with publication number CN115121267A discloses a photocatalytic material of sulfur indium zinc wrapped molybdenum trioxide, as well as its preparation method and application. It combines two semiconductor materials, wide bandgap and narrow bandgap, that is, sulfur indium zinc and molybdenum trioxide are compounded to give full play to their respective advantages to form a heterogeneous structure, which greatly improves the light utilization rate and hydrogen production rate. The Chinese invention patent with publication number CN115121267A provides a BPQDs / MoO3 / ZnIn2S4 ternary heterostructure composite photocatalytic material, preparation method and application. Under light irradiation, the prepared MoO3 / ZnIn2S4 binary heterostructure separates electrons and holes. Due to the energy level difference, the electrons in the conduction band of MoO3 are transferred to the valence band of ZnIn2S4, consuming its holes, accelerating the separation of electrons and holes in ZnIn2S4, and increasing the migration rate of electrons. A Z-type heterostructure is formed between MoO3 and ZnIn2S4, thereby promoting photocatalytic hydrogen production and effectively improving the material's hydrogen evolution ability under visible light of λ>420 nm.
[0005] Based on the properties of the photocatalytic reduction reaction, it seems to be a feasible technical solution to combine MoO3 and ZnIn2S4 to obtain a photocatalyst for catalytic water hydrogen production for photocatalytic CO2 reduction. However, the inventors found that due to the differences in the underlying mechanisms of water hydrogen production and CO2 reduction, the photocatalyst for water hydrogen production prepared with the same MoO3 and ZnIn2S4 components is difficult to meet the functional requirements of CO2 reduction. Water hydrogen production and CO2 reduction are two different chemical reactions. In the water hydrogen production reaction, H2O is electrolyzed or otherwise decomposed into H2 and O2; while in the CO2 reduction reaction, CO2 is reduced to some carbon-based compounds, such as CO, CH4, etc., which usually require external energy input. There are obvious differences in the substrate morphology, intermediate products formed and reduction paths of the two reactions. Therefore, in view of the characteristics of CO2 reduction, the photocatalyst needs to consider the following aspects of parameter adjustment: 1. Design and adjustment of surface active sites; 2. In the CO2 reduction reaction, the influence of electron transmission on the activity of the photocatalyst; 3. Control of specific surface area.
[0006] At present, in the field of CO2 reduction, the driving force of ZnIn2S4-based photocatalysts in inducing the built-in electric field is still insufficient, resulting in the separation efficiency of electrons and holes being difficult to meet the needs of CO2 reduction, thereby limiting the practical application of its photocatalytic performance. In order to overcome this challenge, the present invention is committed to developing a doped ZnIn2S4 photocatalyst with orderly composition and precise structure, in order to optimize the built-in electric field and improve the carrier migration efficiency, thereby greatly improving its photocatalytic performance. This research direction is undoubtedly full of great potential and broad prospects. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, in the first aspect of the present invention, a method for preparing a patterned ZnIn2S4@MoO3 photocatalyst with convenient process and flexible regulation is provided, comprising the following steps: (1) Preparation of rod-shaped molybdenum oxide: 0.5-100 g of molybdate is mixed with 1-700 mL of nitric acid and 10-3300 mL of water, and subjected to hydrothermal reaction at 150-200 °C for 10-20 h; after the reaction is completed, the product is collected, washed and dried to obtain rod-shaped molybdenum oxide; (2) Preparation of patterned ZnIn2S4@MoO3: Mix 0.01-100 g zinc salt, 0.01-100 g indium salt, 0.01-100 g rod-shaped molybdenum oxide, 0.01-100 g sulfur source with 10-3000 mL water; wherein the molar ratio of rod-shaped molybdenum oxide, zinc salt, indium salt and sulfur source is 5:5-20:10-40:24-96; then carry out hydrothermal reaction at 100-150 ℃ for 4-10 h; after the reaction is completed, collect the product, wash and dry it to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
[0008] Based on the above preparation process, the present invention prepares a ZnIn2S4@MoO3 photocatalyst based on S vacancy interface-mediated photocatalytic CO2 reduction by controlling the mass or ratio of molybdate, zinc salt, indium salt, and sulfur source, especially the temperature and reaction time of the two-step hydrothermal reaction. Under the deployment of this process, the ZnIn2S4 nanosheets present a unique vertical growth mode, which not only effectively increases the specific surface area of the material, but also promotes the transmission efficiency of electrons and photons. The nanosheets are firmly anchored on the MoO3 nanorods to form a tight heterojunction interface. This non-uniform surface coverage of the MoO3 nanorods not only enriches the microstructure of the composite material, but also further optimizes its physical and chemical properties by regulating the interface effect.
[0009] At the specific operational level, the effect of hydrothermal reaction temperature or time on the preparation of patterned ZnIn2S4@MoO3 photocatalyst can be reflected from two aspects. In step (1), the dominant influence is the hydrothermal temperature. A higher hydrothermal temperature may destroy the rod-like morphology of the substrate, which will increase the difficulty of subsequent loading of indium zinc sulfide; therefore, the hydrothermal temperature of this step needs to be carefully selected during the preparation process to maintain the morphological integrity of the substrate (specifically, the selection of 150 ℃, 180 ℃, 200 ℃, and the time of 10 h, 15 h, 17 h, and 20 h are particularly suitable parameters for this step). In step (2), changes in hydrothermal temperature and time will affect the thickness of the subsequent loading; extending the hydrothermal time will lead to an increase in the loading amount of indium zinc sulfide, but may cause agglomeration; at the same time, too long a time may cause the nanosheets to grow too thick, which is not conducive to forming a good heterostructure with the substrate (similarly, this step is particularly suitable for selecting temperatures of 100 ℃, 120 ℃, 150 ℃, and times of 4 h, 6 h, and 10 h). Regarding the differences in the performance of the electrochemical photoelectric effect in CO2 reduction, changes in temperature and time during the material preparation process can affect the material structure and performance, and thus affect the performance of the CO2 electrochemical photoelectric effect. High temperature may cause morphological destruction and agglomeration, affecting the surface structure and active site exposure of the material, thereby affecting the CO2 conversion efficiency. Controlling the hydrothermal conditions can affect the material's loading amount, structural stability, and binding with the substrate, thereby affecting the adsorption and conversion efficiency of CO2 molecules on the material surface. In summary, by precisely controlling the hydrothermal temperature and time variables, the structure and properties of the material can be regulated, thereby affecting its performance in the CO2 electrochemical photoelectric effect. Optimizing the preparation conditions can help improve the photocatalytic performance of the material, enhance the CO2 conversion efficiency, and provide better solutions for environmentally friendly energy conversion technologies.
[0010] Ammonium salts and sodium salts are widely available, have low costs, and generally have good solubility and ionization ability in aqueous solution environments, and good reactivity. Therefore, ammonium molybdate and sodium molybdate are very suitable molybdates for the preparation of the present invention. For similar purposes, zinc salts are preferably selected from zinc sulfite, zinc acetate, zinc chloride, and zinc sulfate, which have good water solubility; indium salts can be selected from indium acetate, indium bromide, indium chloride, and indium sulfate; and sulfur sources can be selected from thioacetamide, thiourea, and carbon disulfide.
[0011] Preferably, in step (1), the molybdate includes at least one of ammonium molybdate and sodium molybdate.
[0012] Preferably, in step (1), the concentration of nitric acid is 0.2-1.0 mol / L.
[0013] Preferably, in step (2), the zinc salt includes at least one of zinc sulfite, zinc acetate, zinc chloride and zinc sulfate.
[0014] Preferably, in step (2), the indium salt includes at least one of indium acetate, indium bromide, indium chloride and indium sulfate.
[0015] Preferably, in step (2), the sulfur source includes at least one of thioacetamide, thiourea and carbon disulfide.
[0016] The zinc salt, indium salt and sulfur source are preferably first mixed with water to form a mixed solution and then contacted with the rod-shaped molybdenum oxide. Since the rod-shaped molybdenum oxide is insoluble in water, if mixed too early, some of the raw materials dissolved in water will be adsorbed or precipitated on the surface of the rod-shaped molybdenum oxide in advance under the influence of surface energy, which is not conducive to the reaction to form sheet ZnIn2S4 and the uniform development of the structure.
[0017] Preferably, in step (2), the specific steps of mixing are as follows: mixing zinc salt, indium salt, sulfur source and water to form a mixed solution; then adding rod-shaped molybdenum oxide and ultrasonically treating for 15 min-2 h.
[0018] In the second aspect of the present invention, a patterned ZnIn2S4@MoO3 photocatalyst with high electron transfer efficiency, strong CO2 adsorption capacity and high reduction efficiency is provided. The photocatalyst is prepared by the preparation method of the first aspect of the present invention, and has a structure in which the flake ZnIn2S4 is vertically and alternately loaded on the surface of the rod-shaped MoO3 in a petal shape.
[0019] In the third aspect of the present invention, there is provided an application of the patterned ZnIn2S4@MoO3 photocatalyst according to the second aspect of the present invention, specifically, an application as a photocatalyst in catalyzing CO2 reduction.
[0020] Preferably, the patterned ZnIn2S4@MoO3 photocatalyst is used to catalyze the reduction of CO2 to generate CO and CH4.
[0021] The principle of the present invention is to use the S vacancy interface of the prepared ZnIn2S4@MoO3 photocatalyst with a specific structure to mediate photocatalytic CO2 reduction. It should be noted that in the composite catalyst ZnIn2S4@MoO3, the contribution and mechanism of the S vacancy interface in the water hydrogen production and CO2 reduction reactions are different: 1) The possibility of the S vacancy interface in the composite catalyst: The S vacancy interface refers to the vacancy structure formed by the missing sulfur atoms at certain positions in the crystal lattice; in the composite catalyst, the S vacancy interface may appear, especially on the surface of MoS2 or at the interface with ZnIn2S4. The existence of the S vacancy interface can affect the surface active site distribution and reaction activity of the catalyst, which may have a significant effect on the catalytic performance; 2) The difference in the contribution and mechanism of water hydrogen production and CO2 reduction: In the water hydrogen production reaction, the S vacancy interface provides additional active sites, promotes the adsorption and dissociation of water molecules, and helps to improve the activity and stability of the catalyst; while in the CO2 reduction reaction, the S vacancy interface affects the conversion selectivity and product distribution of CO2 by affecting the adsorption and activation process of CO2 molecules; the two reactions involve different reaction mechanisms and intermediates, and the contribution of the S vacancy interface in water hydrogen production and CO2 reduction is different.
[0022] The inventors studied the mechanism of action of the S vacancy interface in different reactions, which helps to better understand its role in the composite catalyst and provide guidance for further optimizing the catalyst performance. In general, the presence of the S vacancy interface in the composite catalyst has different effects on the water hydrogen production and CO2 reduction reactions. By deeply exploring the mechanism of action of the S vacancy interface in different reactions, we can better understand its influence on catalytic performance and provide more inspiration for optimizing the design of composite catalysts.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for preparing a patterned ZnIn2S4@MoO3 photocatalyst, which adopts a hydrothermal synthesis process and has the advantages of convenient steps and flexible regulation and control, low cost, and is suitable for industrial-scale production.
[0024] The present invention provides a flower-shaped ZnIn2S4@MoO3 photocatalyst, which adopts a structure in which flake ZnIn2S4 is vertically and alternately loaded on the surface of rod-shaped MoO3 in a petal-shaped manner, and has high electron transfer efficiency, strong CO2 adsorption capacity and high reduction efficiency.
[0025] The present invention provides an application of a patterned ZnIn2S4@MoO3 photocatalyst, which has broad application prospects in catalyzing CO2 reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is a scanning electron microscope (SEM) image of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 2 This is a transmission electron microscope (TEM) image of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 3 This is the element mapping spectrum of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 4 The X-ray energy spectrum (energy dispersive spectrometer, EDS) of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 5 This is a transient photocurrent response diagram of the photocatalytic CO2 reduction of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 6 This is the photocatalytic CO2 reduction activity diagram of the patterned ZnIn2S4@MoO3 photocatalyst of Example 1; Figure 7 It is the transient photocurrent response diagram of the photocatalytic CO2 reduction of the patterned ZnIn2S4@MoO3 photocatalyst of Examples 1-3; wherein black corresponds to Example 1, red corresponds to Example 2, and blue corresponds to Example 3. DETAILED DESCRIPTION
[0027] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0028] Example 1 The preparation method of the patterned ZnIn2S4@MoO3 photocatalyst comprises the following steps: (1) Preparation of rod-shaped molybdenum oxide: Weigh 1.4 g of ammonium molybdate, 33 mL of deionized water and 7 mL of nitric acid into a beaker and mix them on a magnetic stirrer at room temperature for 0.5 h; transfer the prepared liquid into a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 180 °C for 17 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain rod-shaped molybdenum oxide; (2) Weigh 1 mmol zinc chloride, 2 mmol indium chloride, 4.8 mmol thioacetamide, weigh 0.5 mmol rod-shaped molybdenum oxide, and measure 20 mL of deionized water; add zinc chloride, indium chloride, and thioacetamide to deionized water at room temperature, stir evenly for 0.5 h at room temperature, then add rod-shaped molybdenum oxide to the mixed solution and ultrasonically treat it for 1 h; transfer the obtained solution to a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 120 °C for 6 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
[0029] The microstructure of the patterned ZnIn2S4@MoO3 photocatalyst prepared in this embodiment was observed by SEM and TEM. The results are as follows: Figure 1 , Figure 2 shown. Figure 1 The scanning electron microscopy (SEM) images of the ZnIn2S4@MoO3 composite material are presented in detail. It can be clearly seen in the figure that the ZnIn2S4 nanosheets present a unique vertical growth mode, which not only effectively increases the specific surface area of the material, but also promotes the transmission efficiency of electrons and photons. In addition, these nanosheets are firmly anchored on the MoO3 nanorods to form a tight heterojunction interface. This non-uniform surface coverage of MoO3 nanorods not only enriches the microstructure of the composite material, but also may further optimize its physical and chemical properties by regulating the interface effect, providing strong support for the application of the material in the fields of photoelectric conversion and catalytic reactions. Figure 2 It shows that the diameter of ZnIn2S4 nanosheets is between 300-700nm, and they are evenly wrapped and tightly anchored on the molybdenum oxide nanorods without self-agglomeration.
[0030] Element mapping was used to characterize the patterned ZnIn2S4@MoO3 photocatalyst. The element mapping results of Mo, S, Zn, O, and In are shown in Figure 2. Figure 3 The EDS was combined with the energy spectrum analysis of the patterned ZnIn2S4@MoO3 photocatalyst, and the results are shown in Figure 4 shown. Figure 3 It shows that all elements are uniformly distributed in the composite material, which also indicates the successful preparation of the composite material. Figure 4 EDS analysis further confirmed the coexistence of Mo, S, Zn, O and In elements in the composite material.
[0031] Example 2 The preparation method of the patterned ZnIn2S4@MoO3 photocatalyst comprises the following steps: (1) Preparation of rod-shaped molybdenum oxide: Weigh 1.4 g of sodium molybdate, 50 mL of deionized water and 10 mL of nitric acid into a beaker, and mix them on a magnetic stirrer at room temperature for 0.5 h; transfer the prepared liquid to a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 180 °C for 17 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain rod-shaped molybdenum oxide; (2) Weigh 2 mmol zinc acetate, 4 mmol indium acetate, 9.6 mmol thioacetamide, weigh 0.5 mmol rod-shaped molybdenum oxide, and measure 20 mL deionized water; add zinc acetate, indium acetate, and thioacetamide to deionized water at room temperature, stir evenly for 0.5 h at room temperature, then add rod-shaped molybdenum oxide to the mixed solution and ultrasonically treat it for 1 h; transfer the obtained solution to a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 150 °C for 6 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
[0032] Example 3 The preparation method of the patterned ZnIn2S4@MoO3 photocatalyst comprises the following steps: (1) Preparation of rod-shaped molybdenum oxide: Weigh 1.4 g of ammonium molybdate, 33 mL of deionized water and 7 mL of nitric acid into a beaker and mix them on a magnetic stirrer at room temperature for 0.5 h; transfer the prepared liquid into a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 200 °C for 10 h; finally, filter the cooled solvent, wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain rod-shaped molybdenum oxide; (2) Weigh 0.5 mmol zinc sulfite, 1 mmol indium sulfate, 2.4 mmol thiourea, weigh 0.5 mmol rod-shaped molybdenum oxide, and measure 20 mL of deionized water; add zinc sulfite, indium sulfate, and thiourea to deionized water at room temperature, stir evenly for 0.5 h at room temperature, then add rod-shaped molybdenum oxide to the mixed solution and ultrasonically treat it for 1 h; transfer the obtained solution to a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 150 °C for 10 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
[0033] Example 4 The preparation method of the patterned ZnIn2S4@MoO3 photocatalyst comprises the following steps: (1) Preparation of rod-shaped molybdenum oxide: Weigh 1.4 g of ammonium molybdate, 33 mL of deionized water and 7 mL of nitric acid into a beaker and mix them on a magnetic stirrer at room temperature for 0.5 h; transfer the prepared liquid into a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 180 °C for 17 h; finally, filter the cooled solvent, and wash the product thoroughly with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain rod-shaped molybdenum oxide; (2) Weigh 1 mmol zinc acetate, 1 mmol indium acetate, 2.4 mmol thioacetamide, weigh 0.5 mmol rod-shaped molybdenum oxide, and measure 20 mL of deionized water; add zinc acetate, indium acetate, and thioacetamide to deionized water at room temperature, stir evenly for 0.5 h at room temperature, then add rod-shaped molybdenum oxide to the mixed solution and ultrasonically treat it for 1 h; transfer the obtained solution to a 100 mL stainless steel polytetrafluoroethylene-lined autoclave and treat it at 120 °C for 6 h; finally, filter the cooled solvent, and thoroughly wash the product with deionized water and anhydrous ethanol, and dry it in ambient air at 60 °C to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
[0034] Example 5 This example is an application example of a ZnIn2S4@MoO3 photocatalyst with a floral pattern. The ZnIn2S4@MoO3 photocatalyst with a floral pattern prepared in the example is used for photocatalytic CO2 reduction. The photocatalytic reduction of CO2 is carried out in a 200 mL custom-made catalytic reactor, which has two openings and is sealed with silicone rubber. A simulated xenon lamp light source (power: 300 W) is placed 10 cm above the photocatalytic reactor. In a typical photocatalytic experiment, 50 mg of the photocatalyst is placed in a glass culture dish with a diameter of 6 cm, and 5 mL of deionized water is added. The catalyst is ultrasonically dispersed for 3 min to form a suspension. The culture dish is placed in an oven and dried at 60 °C. Finally, 500 μL of deionized water is evenly distributed on the surface of the dried catalyst as a hydrogen source for the photocatalytic reduction of CO2. After the system is purified with CO2 at a rate of 30 mL / min for 20 min, xenon lamp irradiation is started. The CO2 photocatalytic reduction product is measured every 30 min using a gas chromatograph flame ionization detector. Under visible light irradiation, the temperature was maintained at about 25 °C by the flow of cooling water and the temperature was measured every 1 h.
[0035] In order to further study the photocatalytic activity of the patterned ZnIn2S4@MoO3 photocatalyst, the inventors recorded the transient photocurrent response of the ZnIn2S4@MoO3 photocatalyst by turning on and off the irradiation lamp for several cycles. The test results are shown in Figure 2. Figure 5 As shown. It is noteworthy that once the light is turned on, anode photocurrent spikes appear in all photocurrent curves, which is due to the large number of recombination of photogenerated electron-hole pairs in the initial stage of illumination. Due to the balance between the separation and recombination of electron-hole pairs, the photocurrent decreases and remains almost constant.
[0036] Figure 6 The photocatalytic activity of ZnIn2S4@MoO3 photocatalyst for CO2 reduction under 350 W xenon lamp (UV-visible light) was demonstrated, with CH4 and CO as the main products. In the absence of light and CO2, the inventors did not find any CO and CH4 in the product, which confirmed that CO and CH4 were actually produced by CO2 under visible light. The ZnIn2S4@MoO3 photocatalyst had a high catalytic CO2 reduction efficiency with a CH4 yield of 20.57 μmol / (h·g) and a CO yield of 10.45 μmol / (h·g) under 7 h of light irradiation.
[0037] This example also studies the transient photocurrent response of the patterned ZnIn2S4@MoO3 photocatalyst of Examples 1-3. The test results are as follows: Figure 7 As shown. It can be more intuitively seen from the figure that Example 1 is the most suitable in terms of control ratio, temperature and experimental time, and Example 1 is the best embodiment of the present invention. In addition, compared with the other two photocatalysts, it can be seen that Example 1 has a stronger photocurrent response, which is strong evidence for excellent CO2 conversion.
[0038] The above test results show that the S vacancy interface mediated photocatalytic CO2 reduction method of the patterned ZnIn2S4@MoO3 photocatalyst proposed in the present invention optimizes the composition and structure of the photocatalyst by comprehensively considering the semiconductor band structure and surface reaction process to improve the conversion efficiency and product selectivity of photocatalytic CO2 reduction. The present invention will use specific element doping, surface modification and other technical means to modify the photocatalyst to reduce the activation energy of CO2 molecules and promote the generation of CO / CH4.
[0039] The ZnIn2S4@MoO3 photocatalyst of the present invention is used for CO2 reduction reaction. The inventors fully considered the following parameter adjustments during the design stage: 1. Design and adjustment of surface active sites: The surface active sites of the ZnIn2S4@MoO3 catalyst are crucial for the adsorption and conversion of CO2 molecules; by adjusting the surface structure, composition and doping of the catalyst, the density and specificity of the active sites are increased, thereby improving the efficiency of CO2 reduction; 2. In the CO2 reduction reaction, the transmission of electrons also has an important influence on the activity of the catalyst; by adjusting the electron transmission properties of ZnIn2S4@MoO3, such as adjusting the electrical conductivity, the electron transmission rate, etc., the reduction activity of the catalyst is improved; 3. Control of specific surface area: The specific surface area of the catalyst directly affects the contact area between the reactant and the catalyst, and thus affects the reaction rate; therefore, by adjusting the specific surface area of ZnIn2S4@MoO3, such as by controlling the grain size, morphology, etc., the efficiency of the CO2 reduction reaction can be optimized. Most importantly, in this process, not only the ZnIn2S4@MoO3 material is generated, but part of the MoO3 will be converted into MoS2 during the synthesis process. The structural advantages such as the number of exposed S edge active sites and the effective electron transfer through the S-Mo-S interface bond jointly promote the excellent photocatalytic performance. Through the fine adjustment of the above parameters, the ZnIn2S4@MoO3 catalyst has higher activity and selectivity in the CO2 reduction reaction, thereby achieving a better catalytic effect. The purpose of this adjustment is to make the catalyst better suitable for the CO2 reduction reaction, give full play to its catalytic performance, and improve the CO2 conversion efficiency.
[0040] As a composite catalyst, the ZnIn2S4@MoO3 of the present invention has a unique composition and structure in the CO2 reduction reaction, which is closely related to its excellent catalytic performance. The following are the unique characteristics of the ZnIn2S4@MoO3 of the present invention and the mechanism related to improving the CO2 reduction effect: 1. Advantages of composite components: ZnIn2S4, as a semiconductor material, has good photocatalytic performance, can absorb light in the visible light range, and promote the photocatalytic reduction of CO2; MoO3 plays the role of electron transmission in the composite structure, which helps to improve the electron transfer efficiency and promote the CO2 reduction reaction; MoS2 has abundant active sites, which helps the adsorption of CO2 molecules and the catalytic reduction reaction; 2. Structural advantages: ZnIn2S4@MoO3 has a heterogeneous structure, which can form abundant interfaces and active sites, which is conducive to the adsorption and conversion of CO2 molecules; The S-Mo-S interface interaction formed between ZnIn2S4 and MoS2 is conducive to the synergistic effect of electron transmission and reaction active sites, and reduces the photogenerated electron-hole recombination, thereby improving the CO2 reduction efficiency. 3. Increase the specific surface area: The composite structure can increase the specific surface area of the catalyst, provide more reactive sites, and enhance the adsorption and conversion capacity of CO2. Therefore, through key improvements to the ZnIn2S4@MoO3 composite catalyst, such as structural optimization and composition regulation, its performance in the CO2 reduction reaction can be enhanced in principle, achieving more efficient CO2 conversion. This improvement will further enhance the activity and selectivity of the catalyst, bringing more promising solutions for applications in the field of CO2 reduction. The effects of this structural or compositional improvement will help improve the competitiveness of the catalyst and enhance its application potential in the CO2 reduction reaction.
[0041] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a patterned ZnIn2S4@MoO3 photocatalyst, characterized in that: The steps include: (1) Preparation of rod-shaped molybdenum oxide: 0.5-100 g of molybdate is mixed with 1-700 mL of nitric acid and 10-3300 mL of water, and subjected to hydrothermal reaction at 150-200 °C for 10-20 h; after the reaction is completed, the product is collected, washed and dried to obtain rod-shaped molybdenum oxide; (2) Preparation of patterned ZnIn2S4@MoO3: Mix 0.01-100 g zinc salt, 0.01-100 g indium salt, 0.01-100 g rod-shaped molybdenum oxide, 0.01-100 g sulfur source with 10-3000 mL water; wherein the molar ratio of rod-shaped molybdenum oxide, zinc salt, indium salt and sulfur source is 5:5-20:10-40:24-96; then carry out hydrothermal reaction at 100-150 ℃ for 4-10 h; after the reaction is completed, collect the product, wash and dry it to obtain a patterned ZnIn2S4@MoO3 photocatalyst.
2. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (1), the molybdate includes at least one of ammonium molybdate and sodium molybdate.
3. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (1), the concentration of nitric acid is 0.2-1.0 mol / L.
4. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (2), the zinc salt includes at least one of zinc sulfite, zinc acetate, zinc chloride and zinc sulfate.
5. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (2), the indium salt includes at least one of indium acetate, indium bromide, indium chloride, and indium sulfate.
6. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (2), the sulfur source includes at least one of thioacetamide, thiourea, and carbon disulfide.
7. The method for preparing the patterned ZnIn2S4@MoO3 photocatalyst according to claim 1, characterized in that: In the step (2), the specific steps of mixing are as follows: mixing zinc salt, indium salt, sulfur source and water to form a mixed solution; then adding rod-shaped molybdenum oxide and ultrasonically treating for 15 min-2 h.
8. A patterned ZnIn2S4@MoO3 photocatalyst, characterized in that: It is made by the preparation method as described in any one of claims 1 to 7, and its structure is that the flake ZnIn2S4 is vertically and alternately loaded on the surface of the rod-shaped MoO3 in a petal shape.
9. An application of the patterned ZnIn2S4@MoO3 photocatalyst as claimed in claim 8, characterized in that: Application as a photocatalyst in catalytic CO2 reduction.
10. The use of the patterned ZnIn2S4@MoO3 photocatalyst according to claim 9, characterized in that: The patterned ZnIn2S4@MoO3 photocatalyst is used to catalyze the reduction of CO2 to generate CO and CH4.
Citation Information
Patent Citations
Mo-doped MoO3@ZnIn2S4 Z system photocatalyst as well as preparation method and application thereof
CN112495401A
Sulfur indium zinc coated molybdenum trioxide photocatalytic material as well as preparation method and application thereof
CN115121267A
Metal oxide-indium zinc sulfide photoelectric catalyst as well as preparation method and application thereof
CN118122344A
Non-noble metal plasma core-shell heterojunction material and preparation method and application thereof
CN118287103A